Research on the Vibration Propagation Characteristics of Non-Uniform Speed Trains Entering and Leaving Stations Based on Field Measurements - Ying Shi; Na Cai; Yekai Chen (Buildings)
Urban rail transit systems, while alleviating traffic congestion, generate environmental vibrations that impact adjacent structures and residents, particularly during train acceleration and deceleration near stations. Existing research predominantly focuses on constant-speed operations, leaving a gap in understanding vibration propagation during variable-speed phases. This study investigates vibration characteristics and propagation behaviors using field measurements from a subway station in Foshan, China. Wireless vibration sensors were deployed across nine measuring points at varying distances (15–35 m) from the subway station’s external wall, capturing time-domain and frequency-domain data during train operations. The analysis incorporated China’s JGJ/T 170-2009 standards, evaluating vibration acceleration levels (VAL) and 1/3 octave band spectra. Key findings revealed background vibrations (0–10 Hz) exhibited negligible interference, whereas vehicle-induced vibrations (40–60 Hz) demonstrated directional disparities: urban-bound trains produced higher accelerations (0.004–0.008 m/s2 vertically) than suburban-bound ones (0.001–0.005 m/s2) due to track damping measures and propagation distance. Vibration attenuation with distance was found to be non-linear, influenced by soil hardening and train speed. Vertical vibrations near the station (15 m) approached the 70 dB regulatory limit, emphasizing proximity risks. Doppler effects were observed during train acceleration/deceleration, though data limitations precluded precise quantification of speed impacts. This work supplements knowledge on non-uniform train-induced vibrations, offering insights for urban planning and mitigation strategies.